Upper limb replantation: surgical strategy and the prophylaxis of acute renal failure due to ischemia reperfusion injury – A report of two cases - Kovačević, Predrag; Kozarski, Jefta; Djordjević, Dragana; Janković, Irena; Pavlović, Dimitrije (Vojnosanitetski pregled, 2023)
Introduction. The arm replantation is an extremely rare and challenging procedure. The recognized risk is myoglobinuria and, consenquently, ischemia reperfusion-induced renal failure. Case report. We presented two patients aged 24 and 46 years who were admitted after traumatic arm amputation. Ischemia time was six and two hours, respectively. Postoperative intensive care treatment with assisted ventilation, sedation, and obtaining sufficient urine output prevented myoglobin-induced renal injury. In the case where ischemia time was shorter, there was only one delayed reconstruction of skin defects after fasciotomy, but in the case where ischemia lasted longer, the patient had two secondary look procedures with acceptable definitive results. Conclusion. Arm replantation is a safe procedure even in cases with longer ischemia time. Postoperative control of urine output, correction of acidosis, and preventing myoglobin-induced tubular injury are crucial for stable postoperative recovery and.
Keywords: hand; intensive care units; reconstructive surgical procedures; replantation; respiration, artificial.